Performance of Reinforced Reactive Powder Concrete Beam-Column Joints under Cyclic Loads - Wenzhong Zheng; Dehong Wang; Yanzhong Ju (Advances in Civil Engineering)
An experimental research was carried out to investigate the seismic performance and shear strength of reactive powder concrete interior beam-column joints subjected to reverse cyclic loads. Four beam-column joint specimens were cast and tested in the investigation. The failure characteristics, deformational properties, ductility, and energy dissipation of reinforced reactive powder concrete interior beam-column joints were analyzed in this paper. The shear strength of joints was calculated according to the GB5001-2010 and ACI 318-14. The results shows that reactive powder concrete beam-column joints have a higher shear-cracking strength and shear carrying capacity and strength degradation and rigidity degradation are not notable. Additionally, the use of RPC for beam-column joints can reduce the congestion of stirrups in joints core. The shear force in the RPC joint is mainly carried by the diagonal strut mechanism; the design expression of ACI 318-14 can be used for calculating the shear strength of RPC joints, which has a safety margin of 22%∼38% in this test.